Comparison of Useful Activities of Improving Awareness in Blended Classes in Java Script and PHP Programming - Miyaji, Isao (International Journal of Educational Technology and Learning, 2018)
The grammar in textbook and program examples are explained in a lecture course on JavaScript programming. It was then followed by explanation with materials describing program examples to practice the grammar and exercise problems. We conducted exercises to prepare programs in exercise problems with reference to the program examples. Instructions were given to complete the program during the lecture course as soon as possible, and the students were asked to submit the program and report files using the functions of e-learning. During the final weeks (Week 14), students were asked to prepare a program of voluntary subject he or she came up with, execute it and evaluate one another. With reference to the results, they were asked to correct them by Week 15 and to evaluate one another again. The useful activities for improving awareness were investigated after the lecture course. This paper reports regarding useful activities for improving awareness. In addition, the result is explained in comparison with the helpful activities in the PHP programming taught in the same way.